Impact of information technology on organisational productivity and employment (a study of manufacturing, logistics, engineering and related service processes). - Sunil Ankalgi. (2008)
This study examines the impact of IT-enabled productivity on employment with specific reference to IT deployment in the manufacturing logistics, engineering, support and related service industries located in Singapore. The study finds that productivity increase over the last 5 years has outpaced employment but increase in business growth has also resulted in sustaining employment.